1974
DOI: 10.1063/1.1681773
|View full text |Cite
|
Sign up to set email alerts
|

Electron scattering from NO and N2O below 10 eV

Abstract: Total electron scattering cross sections for NO and N2O in the energy range 0–10 eV were obtained from exponential attenuation in a straight-line collision chamber without a confining magnetic field. Good agreement is obtained with previous measurements where available. For NO, cross sections have been obtained for the first time for resonance structure in the energy range 0–2.5 eV. There appear to be small, sharp resonances between the large resonances. For both NO and N2O the cross section is observed to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
37
0
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 23 publications
6
37
0
1
Order By: Relevance
“…Despite some qualitative differences bewteen theory and experiment, it is clear that the overall features are properly displayed by these calculations and that the nonlocal model gives a good description of the vibrational excitation dynamics in this system. Figure 6 shows our calculated grand total cross sections (the sum of the integrated elastic and the vibrationally inelastic cross sections) and the experimental measurements of Alle et al [5], obtained by high resolution timeof-flight spectroscopy, and of Zecca et al [32], who analyzed previous experimental measurements ( [3,33]). As can be seen in Fig.…”
Section: A Elastic Scattering and Vibrational Excitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite some qualitative differences bewteen theory and experiment, it is clear that the overall features are properly displayed by these calculations and that the nonlocal model gives a good description of the vibrational excitation dynamics in this system. Figure 6 shows our calculated grand total cross sections (the sum of the integrated elastic and the vibrationally inelastic cross sections) and the experimental measurements of Alle et al [5], obtained by high resolution timeof-flight spectroscopy, and of Zecca et al [32], who analyzed previous experimental measurements ( [3,33]). As can be seen in Fig.…”
Section: A Elastic Scattering and Vibrational Excitationmentioning
confidence: 99%
“…NO is also used as a plasma gas and plays important functional roles in a variety of physiological systems. Although there have been a number of experimental studies on the low-energy behavior of the electron-NO collision cross sections [1][2][3][4][5][6][7][8][9], relatively little has been done on the theoretical front [10,11], particularly in the energy region below 2 eV, which is dominated by negative ion resonances. Calculations in this energy range were initiated in our previous study (Zhang et al [12]), which presented ab initio determinations of elastic and vibrational excitation cross sections using the local complex potential or "boomerang" model, with resonance parameters extracted from electronic fixed-nuclei variational scattering calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Two different types of active spaces were used in our study. The smaller one, referred as (8,12), was of the complete active space variety and included all valence orbitals (3-6 and 1-2 orbitals) and all 12 valence electrons. The larger one, referred as (8 þ 4,12), additionally included 7, 8 and 3 orbitals in the active space.…”
Section: Methodsmentioning
confidence: 99%
“…By using laser photodetachment and photoelectron spectrometry, Siegel et al [4] found the value to be 1.258 AE 0.010 Å . The precision was further improved by Travers et al [5] [7], and 0.054 eV by Zecca et al [12]). Although the experiments also provided additional information for the 1 1 AE þ and 1 1 Á excited states of NO À , the information on spectroscopic constants of these states remain rather limited [7,8].…”
mentioning
confidence: 96%
See 1 more Smart Citation